Determinants Factors Turnover Intention of Employees In Trading and Furniture Manufacture Company - Savira, Brisha; Annas, Mohammad; Tannady, Hendy (Bulletin of Counseling and Psychotherapy, 2024)
In the workplace, workers are crucial to the accomplishment of organizational objectives. As a result, it is critical for businesses to comprehend the variables that may affect employee retention. Employee turnover intention is one element that should be taken very seriously since it can negatively affect the success of the organization. The purpose of this study is to examine the relationship between work engagement, salary satisfaction, training satisfaction, and performance appraisal satisfaction and turnover intention. Quantitative approaches are employed in this study. All of the participants in this study are employees. Through the use of non-probability approaches, particularly judgment sampling, the sample was chosen. There were one hundred samples used in this study. Researchers employed primary data collected through in-depth interviews and the distribution of questionnaires to every employee. The data in this study was analyzed using the SmartPLS 4th edition software. The data analysis results indicate that work engagement is positively influenced by training satisfaction. There is a positive correlation between work engagement and performance appraisal satisfaction. Work engagement is also positively affected by pay satisfaction. Employee turnover intentions are negatively affected by work involvement. Additionally, job engagement positively impacts turnover intentions, acting as a mediator between training satisfaction and work engagement. Work participation serves as a mediator between employee turnover intentions and wage satisfaction, as well as performance appraisal satisfaction, both of which have a positive and significant impact on turnover intentions